Novel insights into indigenous phenol-degrading bacteria from palm oil mill effluent and their potential mechanisms for efficient phenol degradation - Sabri, Izzati; Ng, Kai Xian; Ku Mohammad Soffi, Nabihah; Mohd Yusoff, Mohd Zulkhairi; Nor Muhammad, Nor Azlan; Ho, Li Sim; Maeda, Toshinari; Ramli, Norhayati (Elsevier, 2025)
Phenol is a toxic pollutant with mutagenic, carcinogenic, and teratogenic properties, necessitating its removal from phenol-contaminated environments. Biodegradation presents a viable solution, with microbial sources commonly found in phenol-contaminated environments, including palm oil mill effluent (POME). However, the indigenous bacteria capable of efficiently metabolizing phenol from POME remain unidentified, with limited knowledge of their composition, potential functions, and mechanisms of phenol degradation. The ability of the phenol-acclimatized mixed culture (PBMC) derived from POME to metabolize phenol was assessed by evaluating its bacterial composition using 16S rRNA amplicon sequencing, followed by predictions of its potential mechanisms. Subsequently, the phenol degradation capability was evaluated through batch cultivations with phenol as the sole carbon source. This was then compared with an isolated phenol degrader from POME, identified as Acinetobacter sp. AL9, whose genetic makeup was revealed through whole-genome sequencing. Well-known phenol degraders thrived in the PBMC, including Acinetobacter (16.75 %), Pseudomonas (10.48 %), and Flavobacterium (10.35 %). This community degraded phenol through seven different pathways, primarily catalyzed by protocatechuate 3,4-dioxygenase via the protocatechuate degradation II (ortho-cleavage pathway). The presence of catechol 1,2-dioxygenase and catechol 2,3-dioxygenase also signified the involvement of catechol ortho-cleavage, and catechol degradation I and II (meta-cleavage) pathways, respectively. The PBMC completely degraded 300 mg/L of phenol more rapidly within 16 hours compared to the isolated Acinetobacter sp. AL9, which took 40 hours. This aligns with AL9’s phenol metabolism, which relies solely on the complete catechol ortho-cleavage pathway. This finding highlights the potential for harnessing the indigenous bacterial mixed culture from POME for efficient phenol bioremediation.